Analisis Faktor yang Berhubungan dengan Pemberian MP-ASI di Posyandu Harapan Bunda Dua Desa Tangkit Kecamatan Sungai Gelam - Hamidah, Andi; Radiah, Radiah; Mansyur, Siti Fatimah (Universitas Batanghari Jambi, 2024)
About 40% of children in the world receive only breast milk, while the remaining 60% receive an integral food source when they are under half a year old. This shows that exclusive breastfeeding is still rarely practiced, while early breastfeeding is still common in a number of countries. MP-ASI is food or drink given to babies aged 6 to 2 years to overcome nutritional problems other than breast milk (ASI). At that time, breast milk production was decreasing so that the current supply of breast milk supplements could not meet the increasing nutritional needs of children, so giving it as a complementary food was highly recommended. MP-ASI is additional nutrition for babies, this food must be a supplement and have options to overcome children's problems. This examination is a logical review using a cross-sectional methodology where we only look at examples and at the same time identify elements related to giving MP-ASI. ASI at Posyandu Harapan Bunda Dua, Tangkit City, Sungai Gelam Region in October 2022. The population is 30 respondents with an all out examination of 30 respondents. Chi-square was used in data analysis. 19 respondents (63.4%) had higher education, 24 respondents (80%) did not work, and the same number of respondents had husbands who were supportive or not, 15 respondents (50%) gave MP-ASI to 21 respondents (70%) . There is a relationship between schools, businesses and partner assistance with the provision of MP-ASI at Posyandu Harapan Bunda Dua, Tangkit Sungai Gelam Local City. The conclusion obtained in this examination is that there is a relationship between training, work and partner assistance with the implementation of MP-ASI at Posyandu Harapan Bunda Dua, Tangkit City, Sungai Gelam Region.